Implementing a web‐based introductory bioinformatics course for non‐bioinformaticians that incorporates practical exercises. Issue 1 (13th September 2017) - Vincent, Antony T.; Bourbonnais, Yves; Brouard, Jean‐Simon; Deveau, Hélène; Droit, Arnaud; Gagné, Stéphane M.; Guertin, Michel; Lemieux, Claude; Rathier, Louis; Charette, Steve J.; Lagüe, Patrick
Abstract: A recent scientific discipline, bioinformatics, defined as using informatics for the study of biological problems, is now a requirement for the study of biological sciences. Bioinformatics has become such a powerful and popular discipline that several academic institutions have created programs in this field, allowing students to become specialized. However, biology students who are not involved in a bioinformatics program also need a solid toolbox of bioinformatics software and skills. Therefore, we have developed a completely online bioinformatics course for non‐bioinformaticians, entitled " BIF‐1901 Introduction à la bio‐informatique et à ses outils (Introduction to bioinformatics and bioinformatics tools ), " given by the Department of Biochemistry, Microbiology, and Bioinformatics of Université Laval (Quebec City, Canada). This course requires neither a bioinformatics background nor specific skills in informatics. The underlying main goal was to produce a completely online up‐to‐date bioinformatics course, including practical exercises, with an intuitive pedagogical framework. The course, BIF‐1901, was conceived to cover the three fundamental aspects of bioinformatics: (1) informatics, (2) biological sequence analysis, and (3) structural bioinformatics. This article discusses the content of the modules, the evaluations, the pedagogical framework, and the challenges inherent to a multidisciplinary, fully online course. © 2017 by The International Union of Biochemistry and Molecular Biology, 46(1):31–38, 2018.